Pengaruh Intervensi Menu Seimbang Berbasis Pangan Lokal Papua Barat Daya dengan Dengan Sajian Isi Piringku terhadap Kenaikan Berat Badan pada Balita Gizi Kurang - La Supu; Wilma Florensia (Universitas Malahayati Lampung, 2025)
ABSTRACT Awareness of the benefits of local food in West Papua that meets balanced nutrition with the contents of my plate can increase nutritional intake and weight of toddlers. Factors such as limited access to nutritious local food, lack of knowledge about balanced nutrition and the contents of my plate, and unstable economic conditions are triggers for malnutrition in this region. The purpose o/f this study was to evaluate the effect of a balanced menu intervention based on local food in West Papua with a focus on the application of the contents of my plate model on weight gain in malnourished toddlers in the Remu Health Center Work Area, Sorong City. This study used a quasi-experimental research type with a one group pretest-posttest design. The sample was taken by accidental sampling, namely 30 malnourished toddlers in the Remu Health Center Work Area who received a balanced menu based on local food in West Papua for 1 month with a 7-day menu cycle for one month. The test used was the Paired T-Test with a significance level of  = 0.05. The results of this study indicate that there is an increase in average body weight from 8.430 to 8.670 and the results of the bivariate test show a p value of 0.000 (0.005) or there is an influence of a balanced nutritional menu based on the focus of the contents of my plate according to local food in Southwest Papua with weight gain in undernourished toddlers Keywords: Balanced Menu, Local Food in Southwest Papua, My Plate, Weight Gain in Toddlers ABSTRAK Kesadaran akan manfaat pangan lokal Papua Barat Daya yang memenuhi gizi seimbang dengan sajian isi piringku dapat meningkatkan asupan gizi dan berat badan balita. Faktor seperti keterbatasan akses terhadap pangan lokal yang bergizi, kurangnya pengetahuan tentang gizi yang seimbang dan isi piringku, serta kondisi ekonomi yang kurang stabil merupakan pemicu terjadinya. masalah malnutrisi di wilayah ini. Tujuan penelitian ini adalah untuk mengevaluasi pengaruh intervensi menu seimbang berbasis pangan lokal Papua Barat Daya dengan focus pada penerapan model sajian isi piringku terhadap kenaikan berat badan balita gizi kurang di Wilayah Kerja Puskesmas Remu Kota Sorong. Penelitian ini menggunakan jenis penelitian kuasi eksperimen dengan desain one group pretest-posttest design. Sampel diambil dengan accidental sampling yang merupakan balita gizi kurang sebanyak 30 responden di Wilayah kerja Puskesmas Remu yang menerima menu seimbang berbasis pangan lokal Barat Daya selama 1 bulan dengan siklus menu 7 hari selama satu bulan. Uji yang digunakan adalah uji Paired T-Test dengan Tingkat signifikan a= 0,05. Hasil penelitian ini menunjukkan ada peningkatan rata-rata berat badan dari 8,430 menjadi 8,670 dan hasil uji bivariat menunjukkan nilai p value 0,000 (0,005) atau terdapat pengaruh menu gizi seimbang berbasis focus sajian isi piringku sesuai pangan lokal Papua Barat Daya dengan kenaikan berat badan pada balita gizi kurang. Kata Kunci: Menu Seimbang, Pangan Lokal Papua Barat Daya, Isi Piringku, Kenaikan Berat Badan Balita